Information service of the Foreign bureau of the German trade unions
Suppl. to: Bulletin of the International Federation of Trade Unions ... (ZK 16043). - German ed.: Informationsblatt der Auslandsvertretung der deutschen Gewerkschaften. (ZK 16086). - French ed.: Bulletin d'information de la répresentation extérieure des syndicats Allemands (ZK 16023).